Chasing shadows: a true story of drugs, war and the secret world of international crime - Johnson, Miles (The Bridge Street Press, 2024)
A compulsive true crime thriller about modern-day internationaly drugs trafficking, terrorism and geopolitical intrigue following an investigation driven by one DEA agent, Jack Kelly. Three very different men battle to control their destinies as they hurtle through the hall of mirrors of the global shadow economy LONGLISTED FOR THE CRIME WRITERS' ASSOCIATION 2024 ALCS GOLD DAGGER FOR NON-FICTIONHIGHLY COMMENDED FOR BEST NEW AUTHOR AT THE 2024 TRUE CRIME AWARDS JUDGES' CITATION: 'A cleverly constructed account of three different characters representing different aspects of the ruthless and fierce drugs trade. Never a dull moment. A real page turner... This book is gripping and immerses you in the very real world of the characters.''Read this powerful book by Miles Johnson right now. It will make you realise that what we call terrorism is actually drug trafficking, what we call politics is organised crime and what we call peace is just a truce between mafias.' - Roberto Saviano, author of Gomorrah'McMafia for the new age' Catherine Belton, author of Putin's People: How the KGB Took Back Russia and then took on the West'Compelling, visceral and highly readable' Oliver Bullough, bestselling author of Moneyland'As breathless, complex and on-the-edge suspenseful as the finest thriller fiction - but it's all real, which makes it truly extraordinary' Lee Child'This astonishing and cinematic rollercoaster of a debut will bring Miles Johnson's talent into the brilliant light. Delivered with trademark verve and precision, it achieves that rare and precious thing that is the goal of all great reporting: it reveals the world to itself' Alex Perry, author of The Good Mothers'Miles has used his extensive Italian contacts to get a fully-fleshed out story in the Mafia section; likewise with the Hezbollah characters. He has interviewed over 100 people for the book, including many hours with Jack Kelly, the DEA investigator and hero of the book, which gives us an intimate look at a man dedicated to catching bad guys at the expense of his personal life' Dan McCrum, author of Money MenA compulsive true crime thriller about modern-day international drugs trafficking, terrorism and the mafia following an investigation driven by one DEA agent, Jack Kelly. Three very different men battle to control their destinies as they hurtle through the hall of mirrors of the global shadow economy.Salvatore Pititto is an ambitious Mafia capo working on a vast cocaine shipment who becomes unexpectedly pulled into an arms-smuggling conspiracy. Jack Kelly, a veteran US Drug Enforcement Administration agent, tasked with following a trail of dirty money across continents from a top-secret investigative unit based in Virginia.Mustafa Badreddine is a ghost-like master terrorist wanted by governments across the world who has been secretly dispatched to Syria for his final mission. Each man, born in radically different circumstances in the 1960s, is in his own way grappling with the powerful and unstoppable forces that shape the world around us; forces which topple governments, send refugees fleeing across borders, and put guns in the hands of mercenaries and militias. Each has devoted his whole life to an institution-the DEA, the Mafia and the Lebanese militant group Hezbollah-and each will eventually be destroyed or betrayed by the thing they believe in the most.Set during 2015 and 2016, as the global order began to implode under the pressures of the Syrian civil war and the European refugee crisis, CHASING SHADOWS looks back over the historical conflicts, events and personal histories that have shaped the lives of these three men. It's a book that shows the betrayals, the disillusionment and the violence as Jack Kelly hunts down his targets